Shallow reef fishes around “La Viuda” rocky islet, Golfo Dulce, Costa Rica. - Palacios-Martínez, Gerardo Emigdio (2015)
Rocky reefs maintain a high diversity of organisms. Differences in fish community could be expected by seasonal events and wave action on rocky reefs. I studied “La Viuda” rocky islet, Golfo Dulce, CostA Rica (8°37’33” N - 83°14’08” W) with Bohnsack and Bannerot visual census methods four times between February and December 2002. I identified 28 species and the most abundant families were Pomacentridae and Labridae. Shannon-Wiener diversity was between 1.1 and 1.73 nits/ind., and Pielou 0.43. There is a higher diversity in the dry season and in areas protected from wave action.